Decoding drug tolerance: insights into the Rv0274 gene's role in isoniazid tolerance - Li, Min; Wang, Yun; Xiang, Xiaohong; Dong, Lingling; Li, Qiming; Liu, Zhou; Chu, Wenwen; Naifang, Ye; Gong, Zhen; Zhou, Qiang (Frontiers in Microbiology, 2025)
IntroductionIsoniazid is widely used in the treatment of pulmonary tuberculosis, yet the mechanisms underlying its tolerance remain incompletely understood. The Rv0274 gene of Mycobacterium tuberculosis, presumed to belong to the aldehyde dehydrogenase family, has been hypothesized to contribute to isoniazid tolerance. Mycobacterium smegmatis was used in this study as a surrogate model to investigate this possibility.MethodsWe generated an MSMEG_0608 knockout strain and performed drug susceptibility testing, growth curve analysis, biofilm formation assays, transcriptomic profiling, and RT-qPCR validation. Complementation with Rv0274 and knockdown of MSMEG_0606 were further conducted to substantiate the regulatory relationships observed.ResultsThe deletion of MSMEG_0608 significantly impaired isoniazid tolerance. Complementation and gene knockdown experiments supported the involvement of Rv0274/MSMEG_0608 in modulating the expression of genes associated with Rv0273c/MSMEG_0606, ultimately influencing inhA expression. These findings consistently demonstrated that MSMEG_0608 is integral to the isoniazid tolerance phenotype.DiscussionOur results suggest that Rv0274 (MSMEG_0608) negatively regulates genes linked to Rv0273c (MSMEG_0606), thereby contributing to alterations in inhA expression and influencing isoniazid tolerance. This work provides preliminary mechanistic insight into INH tolerance in mycobacteria and establishes a foundation for further investigations into drug tolerance in Mycobacterium tuberculosis.